Circulating erythroferrone has diagnostic utility for acute decompensated heart failure in patients presenting with acute or worsening dyspnea - Appleby, Sarah; Frampton, Chris; Holdaway, Mark; Chew-Harris, Janice; Liew, Oi Wah; Chong, Jenny Pek Ching; Lewis, Lynley; Troughton, Richard; Ooi, Shirley Beng Suat; Kuan, Win Sen; Ibrahim, Irwani; Chan, Siew Pang; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objectives In dyspneic patients with atrial fibrillation (AF) or obesity, the diagnostic performance of NT-proBNP for acute heart failure is reduced. We evaluated the erythroblast derived protein erythroferrone (ERFE) as an ancillary biomarker for the diagnosis of acute decompensated heart failure (ADHF) in these comorbid subgroups in both Western and Asian populations. Methods The diagnostic performance of ERFE (Intrinsic Lifesciences) and NT-proBNP (Roche Cobas e411) for ADHF was assessed in 479 New Zealand (NZ) and 475 Singapore (SG) patients presenting with breathlessness. Results Plasma ERFE was higher in ADHF, compared with breathlessness from other causes, in both countries (NZ; 4.9 vs. 1.4 ng/ml, p < 0.001) and (SG; 4.2 vs. 0.4 ng/ml, p = 0.021). The receiver operating characteristic (ROC) areas under the curve (AUCs) for discrimination of ADHF were reduced in the NZ cohort compared to SG for ERFE (0.75 and 0.84, p = 0.007) and NT-proBNP (0.86 and 0.92, p = 0.004). Optimal cut-off points for ERFE yielded comparable sensitivity and positive predictive values in both cohorts, but slightly better specificity, negative predictive values and accuracy in SG compared with NZ. In patients with AF, the AUC decreased for ERFE in each cohort (NZ: 0.71, n = 105, SG: 0.61, n = 44) but increased in patients with obesity (NZ: 0.79, n = 150, SG: 0.87, n = 164). Conclusions Circulating ERFE is higher in patients with ADHF than in other causes of new onset breathlessness with fair diagnostic utility, performing better in Asian than in Western patients. The diagnostic performance of ERFE is impaired in patients with AF but not patients with obesity.